TOOL´’N TELL: Visual Essay on Creative Writing - Remelhe, Emílio (Design/Arts/Culture, 2025)
The present visual essay addresses tools of work in the educational domain, specifically within the realm of creative writing. It assumes a metaphorical approach based on an analogy between tools from different fields of activity: it draws a parallel between the operational means of workshop construction and the conceptual means of writing. In this context, ideas such as order, discipline, and organization are still regarded as opposites to creative work. Paradoxically, it is common for the tools, means, and tasks to be perceived by those who use them more as obstacles rather than facilitators. Added to this are stigmas and misconceptions about words, writing, text, and, by extension, books, and authors, whose deconstruction is a workshop task. It is in this sense that the present work is oriented, aiming to create proactive conditions for raising awareness, exploration, reflection, and analysis, seeking to requalify the experience, perception, and self-knowledge. Specifically, it involves recoding a message of awareness to encourage personal and interpersonal engagement in writing, as well as implementing conceptual tools for guided experimental activities.